Exploring The Use of Translation as a Strategy to Learn English - Ajeng Dini Arfianti; Utami Widiati (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: This study primarily wanted to explore students' views and how they employ translation-related strategies to learn English. Five students from the accounting department, Universitas Negeri Malang participate in this qualitative case study. The findings showed that students consider translation has a positive contribution to their English learning. They also mentioned learning activities by using translation that can be categorized into several learning strategies. It is expected that the results of the study can raise awareness and exercise cautious use of translation as an effective learning strategy in English for the benefits of the students. Abstrak: Penelitian ini ingin mengeksplorasi pandangan siswa dan bagaimana mereka menggunakan strategi terkait terjemahan untuk belajar bahasa Inggris. Lima mahasiswa dari jurusan akuntansi, Universitas Negeri Malang berpartisipasi di studi kasus kualitatif ini. Hasil wawancara menunjukkan bahwa siswa menganggap terjemahan memiliki kontribusi positif untuk pembelajaran bahasa Inggris. Mereka juga menyebutkan beberapa kegiatan belajar yang terkait dengan penggunaan terjemahan yang dapat dikategorikan ke dalam beberapa strategi pembelajaran. Diharapkan hasil penelitian ini dapat meningkatkan kesadaran dan melatih penggunaan terjemahan secara hati-hati sebagai strategi pembelajaran bahasa Inggris yang efektif untuk kepentingan siswa.